Globalization and internationalization as frameworks for higher education research. Issue 1 (2nd January 2021) - Tight, Malcolm
ABSTRACT: In contemporary writing on higher education, globalization and internationalization are increasingly popular terms, and they are also increasingly being used as frameworks for higher education research. This article discusses the meaning and application of these terms, documents their usage in higher education research, and critically reviews this research and its usefulness for higher education policy. It concludes that, while many interpret the growing globalization and internationalization of higher education as another effect of neo-liberal agendas, the role of higher education institutions as instigators of further globalization and internationalization should not be ignored, while the compromises they make in doing so need to be acknowledged. It also suggests that higher education researchers themselves need to move out of their national comfort zones and think and research more globally.